Assessing the Interface between Natural Resources, Salafi–Jihādi, and Extremist Groups in Africa since 2009: The Case of Chad and Mozambique - Zicina, Siyakudumisa (University of the Witwatersrand, Johannesburg, 2024)
The catastrophic Salafi–Jihādi attacks of September 11th, 2001, marked the beginning of a vicious cycle of violent extremism across Africa. Since then, Salafi–Jihādi movements in the continent have proliferated in ways unimaginable: from the Sahel, Horn of Africa to Southern Africa. Qualitatively designed, this study examines causal variables that allowed resource-rich African countries to be incubators of Salafi–Jihādi extremism. This inquest is guided by the following research question: what role does Salafi–Jihādi play in starting, perpetuating, and sustaining armed conflict in resource rich states? Thus it explores how Salafi–Jihādi, local extremist groups and the presence/absence of natural resources motivates violent extremism. This investigation theoretically isolates the ‘greed-vs-grievance theory’, instead it aligns itself with the social movement theory to examine conflict in southern Chad and northern Mozambique. This means that other than leaning on a theory that explains the causes of intrastate conflict through the greed-grievance narrative, this study reconsiders the approach in light of insights gleaned from behavioural theories, in particular, the social movement theory (SMT). Thus, the study embraces a theory that seeks to explain why social mobilization manifests (Salafi–Jihādi extremism) maintaining that the SMT provides an interdisciplinary understanding of the causes, dynamics, and nature of intrastate conflict. Other than offering similar but different causal variables, this study finds that the outcome variable – Salafi–Jihādi extremism in Africa materialises from different paths. Variables of ideology, natural resources (scarcity/abundance), illicit activities, foreign actors (colonial powers/private military actors/transnational Salafi–Jihādi groups) and domestic socio-histographies (past-in-the present) were significant factors that resulted into glocal conflicts (expansionism/ separatism) in Chad and Mozambique. In spite of the findings, the study infers that Salafi–Jihādi extremisms within the African continent are movements that occur on the basis of equifinality. The study recommends for dismantling colonial continuities, promotion of good governance, religious coexistence, and youth empowerment.
A research report submitted in fulfillment of the requirements for the Master of Arts in International Relations, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Ansar al-Sunna; Boko Haram; Chad; Glocality; Mozambique; Natural Resources; Salafi–Jihādi; Violent extremism; SDG-8: Decent work and economic growth